AERC-Cornell Symposium on 'Risk, Knowledge and Health in Africa': ARV Treatment and Time Allocation to Household Tasks: Evidence from Kenya - d'Adda, Giovanna (2012)
Using longitudinal survey data collected over a period of two years, this paper examines the impact of antiretroviral (ARV) treatment on the time allocated to various household tasks by treated HIV-positive patients and their household members. We study outcomes such as time devoted to housework, firewood and water collection, as well as care-giving and care-seeking. As treatment improves the health and productivity of patients, we find that female patients in particular are able to increase the amount of time they devote to water and firewood collection. This increased productivity of patients coupled with large decreases in the amount of time they spend seeking medical care leads to a reduced burden on children and other household members. We find evidence that boys and girls in treated patients' households devote less time to housework and other chores. These results suggest that the provision of ARV treatment generates a wide variety of benefits to households in resource-poor settings.